DEVELOPMENT OF THE PERMATA POMAA MODEL TO IMPROVE APPETITE AND REDUCE STUNTING IN TODDLERS TOWARDS A STUNTING-FREE ACEH - Eka Sutrisna; Husna Maulida; Yunita Sari; Yusnidar (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Stunting is a health problem that occurs due to chronic malnutrition in toddlers so that the child's weight and height do not match their age. Efforts to overcome stunting can be done by developing the "Permata Pomaa" stunting alleviation model. This community service aims to develop the "Permata Pomaa" stunting handling model to increase appetite and stunting alleviation in toddlers towards a Stunting-Free Aceh in Jambo Mesjid and Blang Teue Villages, Blang Mangat District, Lhokseumawe City. The activity method is carried out using counseling and training methods on introducing how to provide local-based additional food,child's diet management, toddler food menu and how to cook and serve it, Introduction to baby massage and Tuina massage for stunted toddlers' appetite, community assistance on baby massage and Tuina massage and UMKM assistance. The results of community service showthere is an increase in the average knowledge of participants before and after counseling, the average value of participant knowledge before counseling was 6.97, and after counseling the average knowledge became 11.77. In addition, there is an increase in the weight and height of toddlers, where the average value of toddler weight before the Permata Pomaa community service activity was 10.605 and after the Permata Pomaa community service activity was 10.807, while the average height of toddlers before the activity was 85.964 and after the Permata Pomaa model community service activity was 86.695. There is a difference in the average value between weight before and after the community service activity of 202 grams, while the height difference in mean value is 0.731 cm.